Exercise interventions for patients with heart failure: an evidence map - Wang, Tingting; Ji, Ling; Li, Jian; Zhang, Min; Han, Sixuan; Hong, Yanyan (Frontiers in Sports and Active Living, 2025)
Background and aimsAlthough exercise performance is an essential tool for managing heart failure, there is still no consensus on whether exercise prescriptions can be universally applied to all types of heart failure patients. This study aimed to describe and evaluate the evidence on exercise interventions for patients with heart failure by creating an evidence map.MethodsWe searched PubMed, Web of Science, EMBASE, the Cochrane Library, China National Knowledge Infrastructure (CNKI), Wanfang Database, VIP Database to identify systematic reviews and meta-analysis. We used A Measurement Tool to Assess Systematic Reviews (AMSTAR-2) to evaluate the quality of included systematic reviews and meta-analysis. Bubble charts were employed to visualize key characteristics like intervention effectiveness, literature quality, literature quantity, and heart failure types. Matrix bubble charts were used to show the distribution of outcome indicators, exercise methods, literature quantity, and heart failure types.ResultsA total of 113 systematic reviews/meta-analyses were included and over 80% of studies conclude that exercise is beneficial for heart failure patients. Three heart failure types involved varied due to different classification criteria used in the included literature. Eleven types of exercise interventions have been applied in patients with heart failure and mixed modality exercise is the exercise type with the highest attention. Existing researches focus more on the improvement of exercise capacity and cardiorespiratory function in heart failure patients. Most researchers tend to focus on conducting exercise intervention studies in HFrEF.ConclusionsThe evidence map provides a visual overview of the research volume and findings on exercise interventions for heart failure patients. Exercise interventions have significant advantages for heart failure patients, but there is room for improvement in study quality, heart failure classification, and outcome indicators. Future research should focus on designing more high-quality studies to provide more high-level evidence for this field.